A new approach to provide sustainable solutions for residential sector - Santos, Ricardo (2019)
An energy-efficient appliance normally presents a lower energy con-sumption compared to a less efficient one, with a higher initial investment, alt-hough this not always happens. Additionally, each appliance, presents very dif-ferent features, leading to some difficulties on its choice by the consumer (deci-sion-agent). On the other hand, each consumer, has specific and distinguished needs from other consumers, namely of social, economic or environmental nature. Even by adopting these criteria, this is not an isolated guarantee of an optimal solution for the consumer. It is then necessary to complement this approach with multicriteria, combined with optimization techniques. Evolutionary Algorithms (EA), could be used as an optimization technique, to provide sustainable solutions to the consumer, from the market. In this paper, it’s presented an approach that integrates both concepts, where at the end, it shall be presented a case study, to demonstrate the application of the proposed method.